2011
DOI: 10.1590/s0101-31222011000300017
|View full text |Cite
|
Sign up to set email alerts
|

Germination of cotton seed in relation to temperature

Abstract: -The effect of constant temperature on the germination rate and percentage of two cotton seed lots was determined using a thermogradient plate. A gradient of 10 ºC to 40 ºC was established across the plate so that temperatures changed 2 ºC for each 5 cm increment in length, resulting in sixteen different temperature treatments. The optimal temperature zone for germination was 28 ºC to 30 ºC. As temperature decreased from the optimal zone, the rate of germination also decreased but germination percentages durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…Consistent with the empirically established effects of low temperature on the germination of cotton seeds (Krzyzanowski and Delouche 2011;Khetran et al 2015;Cole and Wheeler 1974), the experimental materials recorded a general reduction in the overall germination, expressed in terms of mean GP, MGT, MDG, PV and GI, concomitant to decreasing temperatures from 30 to 12°C (Table 4). The FA mutants recorded significantly higher mean values for GP, MDG, and GI at all temperature treatments, resulting in a higher, faster and a more uniform germination compared to both GDRS cultivars and landraces.…”
Section: Genetic Diversity Across the Core Gdrs Accessions And Ems Musupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with the empirically established effects of low temperature on the germination of cotton seeds (Krzyzanowski and Delouche 2011;Khetran et al 2015;Cole and Wheeler 1974), the experimental materials recorded a general reduction in the overall germination, expressed in terms of mean GP, MGT, MDG, PV and GI, concomitant to decreasing temperatures from 30 to 12°C (Table 4). The FA mutants recorded significantly higher mean values for GP, MDG, and GI at all temperature treatments, resulting in a higher, faster and a more uniform germination compared to both GDRS cultivars and landraces.…”
Section: Genetic Diversity Across the Core Gdrs Accessions And Ems Musupporting
confidence: 82%
“…Decrease in temperature below 15°C concomitantly reduces germination percentage and induces chilling injuries that often leads to seedling malformations, taproot loss, reduced vigor, increased occurrence of seedling diseases, poor stand establishment and ultimately, reduced yields. Similarly, low temperature stress at the later stages of growth negatively impacts the crop by delaying fiber elongation and reducing cell wall thickening, resulting in low cellulose production and overall decline in crop productivity (Kittock et al 1986;Speed et al 1996;Krzyzanowski and Delouche 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum seed germination, vigor index occurred at 20-30°C and these temperature regimes were identified as optimum for wheat seed germination. The delay in germination percentage and the reduced germination percentages were observed in Gossypium hirsutum at LT below 20°C [105]. In T. aestivum, the germination is drastically hampered at temperature below 8-10°C [106].…”
Section: Germinationmentioning
confidence: 99%
“…According to the experiments on cotton germination, the germination rate can reach 90% in the laboratory [29]. The mean germination rate of this field study was 56.26%, as presented in Section 4, indicated that the study field has a low germination rate.…”
Section: Discussionmentioning
confidence: 62%